2022
DOI: 10.3389/fpubh.2022.1049822
|View full text |Cite
|
Sign up to set email alerts
|

Association of psychological symptoms with job burnout and occupational stress among coal miners in Xinjiang, China: A cross-sectional study

Abstract: ObjectiveThe study aimed to investigate the influencing factors of psychological symptoms in relation to job burnout and occupational stress among coal miners in Xinjiang, so as to provide data support for enterprises in an effort to help them identify internal psychological risk factors and improve the mental health of coal miners.MethodsA cross-sectional study was carried out. A total of 12 coal mines were selected using the stratified cluster random sampling method and 4,109 coal miners were investigated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…For miners, occupational risk hinders job performance and increases psychological problems, such as anxiety [ 96 ]. Problems related to work execution, such as dangerous working environments and high job complexity, continuously plague miners’ job performance [ 97 ]. Therefore, these research findings support H2a, H2b, and H2c.…”
Section: Discussionmentioning
confidence: 99%
“…For miners, occupational risk hinders job performance and increases psychological problems, such as anxiety [ 96 ]. Problems related to work execution, such as dangerous working environments and high job complexity, continuously plague miners’ job performance [ 97 ]. Therefore, these research findings support H2a, H2b, and H2c.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study found that the incidence of occupational stress among railway workers in Fuzhou City was 50.58%, which was lower than that of employees of medical staff (59.4%) [ 35 ] and higher than coal miners (38.1%) [ 36 ]. The higher occupational stress scores in the age < 25 years and working experience < 5 years group are consistent with the findings of Ines et al [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may since this group of workers are new to their jobs, have heavy workloads, are inexperienced, and encounter more difficulties and challenges [ 38 ]. The incidence of job burnout among participants was 93.47%, which was higher than that of caregivers (67.37%) [ 39 ] and coal miners (77.74%) [ 36 ]. The higher burnout scores in the age group of 35–45 years old and 10–20 years of service are consistent with the results of Xian et al [ 40 ], which may related to the fact that this group of workers has been in the job for a long time, but their career development is different from what was envisioned, and their professional enthusiasm diminishes due to a lower sense of professional identity.…”
Section: Discussionmentioning
confidence: 99%